The Explorational Analysis of the Digital Transformation Challenges in the Freshwater Fisheries Industry in Central Java Province Through Group Concept Mapping: a Digital Business Ecosystem Perspective - Kusuma Wardhani, Shinta; Noviaristanti, Siska (Riviera Publishing, 2023)
This research explores the perspective of the challenges of digital business ecosystem players who utilize digital technology in the freshwater fisheries industry in Central Java. Methodology Obtained from ecosystem actor informants through interviews. This research falls under the mix method criteria where qualitative challenge analysis is carried out from triple helix sources (government, universities and industry) which produces challenge clusters so that they are qualitative in nature. natural. in nature. Research can be carried out on SME respondents using number 8. These SMEs assess clusters based on what they face and the obstacles that exist in their industry. Through this mixed method more comprehensive results were obtained, validating the challenge statement. The results of the research show critical clusters that are important and deserve attention for assessing the current situation through quadrant distribution graphs, namely Attitudes and SME Business Actors in Utilizing Digital Business Technology, Business Actors' Mindsets towards Digital Business Technology, Evaluation of Government Support, and Business Readiness Technology Digital. thus creating change for the better as a form of future strategy that is neater and more distributed according to the needs of the actors. Research implications: Data collection using interviews with the group concept mapping method limits researchers in confirming results and invites grouping of collected challenge statements so that the GCM method is not recommended for small studies. In addition, the greater the number of respondents, the more valid the results are for various SME conditions.